Design of a Mobile Application for Disaster Management and Examination of the Suitability of Emergency Meeting Areas with GIS: The Case of Konya Province - Büşra Kart; Ceren Yağcı; Büşra Gözgörer; Efsun Avcı; Fatih İşcan (Doğal Afetler ve Çevre Dergisi)
Turkey is located in the Alpin Earthquake Belt, one of the most active seismic belts in the world. The community is greatly affected by earthquakes due to its location. Especially since the 1999 Marmara earthquake the role of disaster management has risen and, in this respect, use of mobile apps has grown in popularity in Turkey. In this study, an Earthquake Information System Mobile Application was designed using Flutter programming language on Android Studio software and distribution of emergency meeting areas of Konya province over the city was investigated using GIS. The suitability of existing emergency meeting areas was evaluated on the maps with the criteria of acreage, population, accessibility and proximity of settlements. The aim of this application is to raise disaster management awareness in the public. Various earthquake management contents were used in the mobile application before, during, and after the earthquake. The most different aspect of this application is represented by instant location data of users and emergency meeting areas. Thus, with mobile application the closest emergency meeting area information can be accessed instantly in a moment of panic. In addition, the application can help to avoid panic during the process until the temporary shelter is ready after the earthquake, allowing for more effective communication, collaboration, and providing a faster first emergency aid. With this study, it was concluded that 125 emergency meeting areas in Konya (including districts) will meet the needs according to the criteria of this study of settlements of a disaster.